Serum Calcium Status of Neonates with Seizure in a Tertiary Care Hospital (Bangladesh Journal of Child Health, 2013)
Background: Seizure is a common neurological disorder in neonatal age group. Primary metabolic derangement is one of the common reason behind this convulsion during this period. Among metabolic abnormalities, hypocalcaemia is most common followed by hypoglycemia and hypomagnesaemia. Objectives: The present study was carried out to assess calcium status in the serum of neonates with convulsion, where no obvious cause of convulsion was found. Methodology: This prospective case control study was conducted in the neonatal ward of Dhaka Medical College Hospital over one year from July 2003 to June 2004. A total of 50 neonates (1- 28 days) who had convulsion but no apparent reasons of convulsion had been found out, were enrolled as cases and 50 age, sex body weight matched neonates who had no history camalnia admitted cases of were enrolled as controls. After a quick clinical evaluation and control of convulsion and before giving any specific treatment serum calcium status was measured by colormetric determination (O- CRE-SOL Phahalein complex) method. Neonatal hypocalcemia is considered if serum calcium value less than1.75 mmol/L (7 mg/dl). Results: Among a total of fifty cases, 60% had hypocalcemia, and about 20% of controls also had low calcium level without any manifestation. The mean serum calcium level of cases and controls were 1.62 ± 0.29 and 2.07 ± 0.03 mmol/l respectively (p